Predictive Model of the Psychological Well-Being of Nursing Students During the COVID-19 Lockdown - Tânia Marlene Gonçalves Lourenço; Ana Catarina Rodrigues da Silva Reis; Enrique Jesús Sáez Alvarez; Rita Maria Sousa Abreu-Figueiredo; Zaida Borges Charepe; Goreti Marques; Maria Luísa Vieira Franco Gonçalves (SAGE Publishing, 2022)
Introduction Lockdowns due to the COVID-19 pandemic radically changed nursing education. Along with social isolation, the transition to distance education affected the well-being of students in several countries, particularly Portugal and Spain. Objectives To identify which variables are predictors of psychological well-being for Portuguese and Spanish nursing students during mandatory lockdowns. Methods A multicenter, cross-sectional, descriptive, correlational study involving a sample of 1075 students (944 women, mean age 22.46 + /−4.95 years). Data were collected from an online questionnaire which applied the following scales: Perceived Stress Scale (α = .820); Brief COPE-14 Subscales (α = .430 < 0.930); Well-being Manifestations Measure Scale (α = .940); Herth Hope Index (α = .850). A multiple regression model was created to predict the psychological well-being of nursing students. Results The following predictor variables were identified in the model of the psychological well-being of students during the COVID-19 pandemic: perceived stress ( β  = .405; p  ≤ .001); hope ( β  = .404; p  ≤ .001); and the mechanisms of active coping ( β  = .405; p  ≤ .001), planning ( β  = .097; p  ≤ .001), and positive reinterpretation ( β  = .053; p   =  .12). These five variables predicted 62.0% of the nursing students' psychological well-being ( R 2  = .620; F  =  350.82; p  ≤ .001). Conclusion Promoting students' mental health is essential, especially in periods of great adversity, such as a pandemic. Our results lead the way for the design and validation of an intervention program that addresses the five variables identified as predictors of students' psychological well-being.